MICROPLASTIC-DRUG INTERACTIONS: UNVEILING COMBINED EFFECTS ON BIOLOGICAL SYSTEMS - KRANTHI YALLA; SRINIVASA RAO ATLA; YOHAN GANGOLU; KRISHNA PRIYANKA KOYA; SRUTHI GANTA; SUDHEER YARRA; KIRAN MANDA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
In our daily life plastic plays a major role in packaging material, clothing, construction, electrical, transportation, and medical devices because of their affordability, light weight, and availability. The most commonly used plastics are Polypropylene, Polyethylene, Poly hydroxyl alkanoates, Polystyrene, Poly vinyl chloride and Polyamide. Some experts estimate that the total amount of plastics produced worldwide increased at an annual growth rate of 5% was observed from 1950 to 2018 amounted to 359 million tons; about 10% of that amount is ending up in the ocean through various channels. In 2018, worldwide plastic output hit 360 million tons, with just 6% - 20% recycled. Regretfully, plastic usage is increasing. Although they are susceptible to ultraviolet light and mechanical worn they did not worn away. These Microplastics are abundantly found in the environment which paved a way to toxic environment. Because of their tiny size, large specific area, hydrophobicity, and stabilized chemical properties, MPs can endure in the environment for hundreds or even thousands of years. Microplastics are classified into two types: degradable and non-degradable. In this review, we demonstrate the interaction between Micro, Nano plastics with drugs and their effect on environment. Many drugs like Boron, Tetracyclines, Methamphetamine, Ciprofloxacin, Amphetamine, Chlortetracycline, Procainamide and Doxycyclines with Micro and Nano plastics shows negative impacts on living organisms directly or indirectly. This review will brief some of the reported impacts on living organisms.